2011
DOI: 10.1021/bm200390a
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Starch Dissolution and Gelatinization

Abstract: The disruption of starch granular structure during dissolution in varying concentrations of N-methyl morpholine N-oxide (NMMO) has been studied using three maize starches with varying ratios of amylose and amylopectin. Behavior in NMMO has been characterized by differential scanning calorimetry (DSC), microscopy, rapid viscosity analysis (RVA), and rheometry. Exothermic transitions were observed for the three starches in both 78 and 70% NMMO; the transition changed to an endotherm at 60 and 50% NMMO. Consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 36 publications
10
32
0
Order By: Relevance
“…When heating is continued in the hot stage, after 20 min at 95 • C, nearly all the granules disappear. This again indicated the process is kinetically controlled, as found for maize starch and reported in Koganti et al (2011).…”
Section: Samplesupporting
confidence: 80%
See 2 more Smart Citations
“…When heating is continued in the hot stage, after 20 min at 95 • C, nearly all the granules disappear. This again indicated the process is kinetically controlled, as found for maize starch and reported in Koganti et al (2011).…”
Section: Samplesupporting
confidence: 80%
“…Potato and tapioca starches, which do not contain any native lipids, exhibited higher enthalpies than cereal starches. All starches exhibited exotherms in 78% NMMO, which has been interpreted as a sign of strong polymer-solvent interaction and further dissolution of starch granules as explained in Koganti et al (2011). It can be seen that all starches had higher onset temperatures in 78% NMMO than in water.…”
Section: Samplementioning
confidence: 68%
See 1 more Smart Citation
“…Starch gelatinization has been studied for a long time (Olkku and Rha, 1978;Donovan, 1979;Ratnayake and Jackson, 2006), essentially in water, but also more recently in other liquids, like glycerol , NMMO (Koganti et al, 2011(Koganti et al, , 2015 and ionic liquids (Liu and Budtova, 2013;Mateyawa et al, 2013Mateyawa et al, 2013. Different methods were used to characterize gelatinization kinetics and mechanisms, like differential scanning calorimetry (DSC), optical and electron microscopy, birefringence, wide angle X-ray diffraction, light scattering, viscosity measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that small amounts of water can dramatically influence the liquid properties of ionic liquids, in particular the diffusion coefficient, viscosity, polarity and surface tension of ionic liquids (Kohno & Ohho, 2012 with G50 and G80. The gelatinization and swelling properties of starches are known to be influenced by the amylose and amylopectin ratio in the starch (Koganti, Mitchell, Ibbett & Foster, 2011). A series of investigation with maize starches containing varying amylose contents indicated that gelatinization temperatures increased with increasing amounts of amylose using the DSC.Without heat (at room temperature), only the low amylose starches are susceptible to gelatinization.…”
Section: Ftir Spectroscopymentioning
confidence: 99%